CREATIVE BRAINSTORMING TECHNIQUES IN GROUP GUIDANCE - Habsy, Bakhrudin All; Zainiah, Nisrina Salwa; Saleha, Aula Niswa; Pagho, Amanda Agustin Putri; Merivasari, Chelvi Agusty (Jurnal Kajian Pendidikan dan Psikologi, 2024)
Group guidance services are services provided to a group of individuals, where they together get information from sources, especially mentors or counselors, which help them in their daily lives and in making decisions. Group guidance helps students in planning a future that suits their talents, interests, and aspirations. The service aims to stimulate the development of feelings, thoughts, perceptions, insights, and attitudes that support more effective behavior change, including improving verbal and nonverbal communication skills for students. One way that can be used in group guidance is the brainstorming technique. The research method used is a qualitative description with a literature study. The results of the study explain (1) the definition of brainstorming technique, which is a technique used to create a long list of different answers without assessing individual ideas. (2) The rules and also the purpose of the brainstorming technique (3) The steps of performing the creative brainstorming technique by exchanging diverse thoughts between students. (4) Stages of using solve problems so that creative ideas will be found from various points of view that will overcome the difficulty of the problem through fun and relaxing activities.